High oxygen permeation through A-site deficient K2NiF4+δ-type oxide hollow-fiber membrane. Issue 9 (15th June 2018) - Liao, Qing; Zhuang, Libin; Wei, Yanying; Xue, Jian; Wang, Haihui
Abstract: A U-shaped hollow-fiber membrane of A-site deficient K2 NiF4+δ -type oxide (Pr0.9 La0.1 )1.9 (Ni0.74 Cu0.21 Ga0.05 )O4+δ ((PL)1.9 NCG) was developed through the phase inversion spinning method. At 975 °C, 2.51 mL/min cm 2 oxygen permeation flux can be achieved under air/He. And stable oxygen permeation performances were obtained during the 285 h long-term tests. The electrical conductivity, surface morphology and oxygen permeation properties of (PL)1.9 NCG hollow-fiber membrane were studied in detail. Graphical abstract: A high oxygen permeation flux of 2.51 mL/min cm 2 is obtained under the gradient of air/He at 975 °C through the A-site deficient (Pr0.9 La0.1 )1.9 (Ni0.74 Cu0.21 Ga0.05 )O4+δ ((PL)1.9 NCG) U-shaped hollow-fiber membrane, which is three times higher than that of the (PL)1.9 NCG disk membrane (0.6 mm) and twice higher than that of the cation-stoichiometric (Pr0.9 La0.1 )2.0 (Ni0.74 Cu0.21 Ga0.05 )O4+δ hollow-fiber membrane.